Pendidikan Karakter dalam Perspektif Pendidikan Islam - Tola, Baso (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
This writing is aimed to analysetheeducational character building according to Islamic education perspective. Since a man came upin the world, they have been equipped with spiritual potency such as mind of thinking, heart, desire, soul, and physic potency. All the potencies will develop in accordance to the stimulus which is given through education. The human mind will be smart and can be used to solve the problems, when it is educated, charged with intellectualexercises and filled it with many kinds of knowledge, in turns it will bear intellectual question. The human heart will get emotional and spiritual question, when it is given education, then they will get their emotional and spiritual question. Moreover, the desire, as motoric power, has a positive meaningas long as it is educated. Surely, the desire can be controlled.